Why we must have a "scientific psychology" how do we "come to know" what we take as our knowledge? - Parrott, George (НТУ "ХПІ", 2017)
It is argued here that all knowledge and Psychology especially needs to be scientifically based to avoid the biases of more personal opinions about behavior. Examples of conclusions about child development, empathy, helping, memory, psychopathology and individual differences are discussed to support the use of good science vs. personal opinion on creating knowledge about behavior.
Keywords: behavior; individual differences; personal opinion; modern science